THE USE OF SONG LYRIC MEDIA IN LEARNING LISTENING SKILL FOR 11TH GRADE STUDENTS IN MAN 1 SINJAI UTARA - Syarifah Ummul Khaeri; Haryanto Atmowardoyo; A. Muliati (Universitas Negeri Makassar, 2022)
The objective of this research is to find out whether or not song lyric media increase students’ listening skill. This research is a pre-experimental design with one class experimental. The researchers choose class 7A as the sample which consists of 26 students, 11 male and 15 females. The researchers use purposive sampling technique because from the class has the most active students in daring class. The pre-test and post-test consist of 30 numbers contains 20 words to translate and 10 words to match meaning that represent noun, adjective and verb. The results of pretest show that the mean score of pre-tests is 44.19 with standard deviation 11.35 and standard error 2.23. There are also 2 students classified into fairly category,3 students classified into poor category, 21 students classified into very poor category. The classification shows that students still have lack of vocabularies, because they are still beginner in learning English. In contrast, the results of posttest show that the mean score of 26 students in post-test is 82.04 with standard deviation 6.71 and standard error 1.32. There are 5 students classified into very good category, 19 students classified into good category, and 2 students classified into fairly category. In addition, the t-test value is higher than t-table value (27.474>2.059). It means that the nursery rhyme videos increase students’ vocabulary mastery.